Association of angiogenesis and inflammation-related gene functional polymorphisms with early-stage breast cancer prognosis - Korobeinikova, Erika (Oncol Lett, 2020)
Genetic variations in inflammation- and angiogenesis-related genes may alter the coded protein level and impact the pathogenesis of breast cancer (BC). The present study investigated the association of functional single nucleotide polymorphisms (SNPs) in the VEGFA, IL-1β, IL-1α and IL-6 genes with the early-stage BC phenotype and survival. Genomic DNA and clinical data were collected for 202 adult Eastern European (Lithuanian) women with primary I–II stage BC. Genotyping of the SNPs was performed using TaqMan SNP genotyping assays. Nine VEGFA, IL-1β, IL-1α and IL-6 polymorphisms were analysed. The VEGFA and IL-6 haplotypes were inferred using Phase software. Patients were prospectively followed-up for recurrence, occurrence of metastasis and mortality until April 30, 2019. All studied genotypes were in Hardy-Weinberg equilibrium and had the same distribution as the 1,000 Genomes project Phase 3 dataset for European population. Significant associations of the studied SNPs with clinicopathologic variables were observed between IL-1α rs1800587 C allele and larger primary tumour size; IL-6 rs1800797 A allele, rs1800797 GA genotype, rs1800795 C allele, IL-6 (rs1800797-re1800795) AC diplotype and hormonal receptor-positive disease; IL-6 rs1800797 A allele and HER2 negative status. In univariate Cox survival analysis, IL-1α rs1800587 CC and IL-6 rs1800797 GG genotype carriers exhibited worse disease-free survival (DFS), metastasis-free survival (MFS) and overall survival (OS). The IL-6 rs1800795 GG genotype was associated with worse OS. IL-6 (rs1800797, rs1800795) GG/GG diplotype carriers had shorter MFS and OS. Multivariate Cox survival analysis revealed that the IL-1α rs1800587 CC genotype was an independent negative prognostic factor for DFS, MFS and OS, and the IL6 GG/GG diplotype was an independent negative prognostic factor for MFS and OS. According to the present study, functional SNPs in the IL-1α and IL-6 genes may contribute to the identification of patients at higher risk of BC recurrence, development of metastases and worse OS among early-stage patients with BC.